Posthumanizm, transhumanizm, antyhumanizm, metahumanizm oraz nowy materializm. Różnice i relacje = Posthumanism, transhumanism, antihumanism, metahumanism and new materialism. Differences and relations - Ferrando, Francesca (Zielona Góra: Lubuskie Towarzystwo Naukowe)
"Posthuman" has become the term that embraces (philosophically, culturally and critically) posthumanism, transhumanism (together with such currents as extropianism, liberal and democratic transhumanism), new materialism (unique, feminist movement within the realm of posthumanism) and also diversified panorama of antihumanism, posthumanisms and metahumanisms. The general use of this term tries to cover all its multiple meanings, to grasp the whole, general problematic, however its generality leads to the methodological and theoretical confusion among the laics, as well as the experts. This essay is an attempt to explain the differences between these movements. The attention has been focused on the area of meanings common to them.
Keywords: posthumanizm; transhumanizm; antyhumanizm; metahumanizm; nowy materializm; technologia; przyszłość; postczłowiek; transczłowiek; cyborg; posthumanism; transhumanism; antihumanism; metahumanism; new materialism; technology; future; posthuman; transhuman